IDENTIFICATION OF BREATHING FREQUENCY IN PREDICTING MORTALITY OF HEAD INJURY PATIENTS - Rahmawati, Ika; Sulistyawan, Agus (Jurnal Wiyata Penelitian Sains dan Kesehatan, 2020)
Background : Head injury was the highest prevalence of trauma and was one of the main causes of death and disability. Head injury patients often experience increased respiratory rate. Head injury patients with fast respiratory rate had a worse prognosis. The occurrence of hyperventilation could be caused by intracranial disorders. Hyperventilation that occurs due to increased intracranial pressure on head injury could be fatal. A poor prognosis in head injury patients can also occur when the respiratory rate is less than 10 times per minute due to decreased perfusion to the brain and decreased oxygenation (Oertel, et al, 2002). Objective : Â This study aim to determine whether the respiratory rate can predict the mortality of head injury patients. Methods : The research design used was cross sectional. The sampling technique used was accidental sampling with a total sample of 30 respondents. The measuring instrument used was an observation sheet. Result : The results of the analysis using the Spearman rho test showed a significance value of 0,000, which means there is a relationship between respiratory rate and mortality of head injury patients. Head injury patients who experience increased respiratory rate, then the mortality will increase. Conclusion : Based on the explanation above, can be concluded that the respiratory rate can be used to predict the mortality of head injury patients.